Book Review of the Women in the Legislation Arena in Iran (1285-1395) - Alireza MollayeeTavani; Sareh Asgari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews the book “Women in the Legislation Arena in Iran (1285-1395)” written by Manchoohr Nazari. This book is one of the rare studies on the topic of women suffrage, so it is of great importance. The main formal critique of this book has to do with plagiarism mainly because the author has not followed the rules in citations, and many of the references are either missing or faulty. Despite the reachability of the first-handed documents, in many cases, the secondary documents have been cited, and in some cases, the secondary references have been intentionally dismissed, and the author has cited them as the first-handed document directly. The main content-based shortcomings are as follow: inconsistency of title with content, the loss of the first- handed references such as documents, extended negotiations, periodicals, memories, formal reports, and simultaneous historiography, ignoring other events and variables leading to the suffrage of women in the span of 57 years, missing to analyze some events and delivering very hurried, a superficial and skimming overview of the many of influential events and opinions, as well as proposing some contradicted demonstrations. Considering all the formal and content-based aspects of this book, it could be concluded that the book, despite its pompous title, has failed to sketch out an accurate account of events leading to the suffrage of women.